Interrelationship between processes of economic security intellectualization and ensuring sustainable development of the enterprise in the conditions of macroeconomic systems transformation - M. V. Shashyna; O. V. Kostiunik; M. O. Dergaliuk; О. S. Solosich; O. V. Ocheretiana (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2024)
This article is devoted to the systematization of the theoretical and applied aspects of the qualitative relationship between the processes of economic security intellectualization and ensuring the sustainable development of entrepreneurial entities, the integration of the conceptual provisions of these theories into the system of organizational and economic support for the activities of enterprises under the influence of active transformations of modern macroeconomic systems. The authors analysed in detail the applied features of the intellectualized approach implementation to the formation of economic security policy for business structures. The system provisions of the implementation for the conceptual foundations of sustainable development theory in the economic processes of the enterprises functioning are singled out. The fundamental principles of qualitative integration of the processes of economic security intellectualization and ensuring the sustainable development for entrepreneurial entities are formulated, in particular the principle of purposefulness, the principle of innovation, the principle of humanism, the principle of responsibility, the principle of balancing, the principle of synergy, the principle of participativeness, the principle of transparency, the principle of knowledge preservation. The proposed logical-structural diagram of the interconnection between functional aspects of the economic security intellectualization processes and ensuring sustainable development at the enterprise level, which qualitatively coordinates the relevant functional processes (financial, personnel, technical and technological, informational, etc.), which reflect the practical manifestations of the intellectualized approach implementation in economic security and direct sustainable development of the enterprise. The component-by-component integration of the system processes of economic security intellectualization and ensuring sustainable development is presented, which reflects the relationship of benchmark elements on each of the concepts within the management structure of economic entities. A component-by-component analysis of instrumental support was carried out in terms of specific management practices of an intellectualized approach to ensure the enterprise economic security within the system elements of the sustainable development theory based on a three-unit approach (economic component, social component and environmental component).